Towards the open eco-innovation mode: A model of open innovation and green management practices - P. Naruetharadhol; W. A. Srisathan; N. Gebsombut; C. Ketkaew (Cogent Business & Management, 2021)
Small- and medium-sized enterprises (SMEs) have played an income-generating role in economic notions of prosperity in many developed countries, especially Thailand. Inside green economy, fostering eco-innovation by open innovation has become an increasingly new normal issue in Thailand. The ability to identify and collaborate with external knowledge sources and eco-innovative characteristics of SMEs is of essence to policy-makers and firm practitioners. This paper aims to shed the new light on the adoption of open innovation into eco-innovation which leads to the open innovation mode. Simultaneously, eco-innovation requires green management practices to interact with the concept of open innovation. Through structural equation modelling, 636 firms were collected and employed to estimate the proposed model. The prominent results verify: (1) open innovation significantly affects eco-innovation, which allows to obtain the open eco-innovation mode, and (2) open innovation through green management practices contributes significant benefits to eco-innovation. Based on the evidence, policy-makers and firm practitioners can improve the open eco-innovation model by integrating open innovation and eco-innovation with green management practices in their strategic planning and decisions.
Keywords: 650; open innovation; eco-innovation; the open eco-innovation; green management practices; Thailand; SMEs